Expression Profiling of Lipolytic and Long-Chain Fatty Acid Biosynthesis Genes in Catfish Larvae Fed With Graded Lipid Levels - Ishfaq Nazir Mir; P. P. Srivastava; Irfan Ahmad Bhat; Jaffer Yousuf Dar; Deepak Agarwal (Frontiers in Marine Science, 2020)
This study was designed to evaluate the effect of dietary lipid levels on the mRNA transcripts of lipid metabolic regulatory genes. Nine combinations of experimental diets containing graded lipid (80, 100, and 120 g/kg) and protein (450, 500, and 550 g/kg) levels were fed to the Clarias magur (Indian walking catfish) larvae from 14 to 35 dph (day post hatching). All the lipolytic genes, such as pancreatic triacylglycerol lipase (PL), lipoprotein lipase (LPL), and bile salt-activated lipase (BAL), and genes for long-chain polyunsaturated fatty acid (LC-PUFA) biosynthetic enzymes like fatty acyl desaturase-2 (FADS2), fatty acyl desaturase-5 (FADS5), and elongase (ELOV) were expressed in a wide range of tissues. A high abundance of mRNA transcript levels of lipolytic genes was detected in the intestine and liver, and similarly, desaturases and elongase were predominantly found to be expressed in the liver, brain, and intestine. Among the diets, a significantly high expression of both lipolytic and LC-PUFA biosynthetic genes were observed at 8% dietary lipid level. The mRNA expression of all the studied genes was down-regulated at 12% dietary lipid contents. Hence, the present study concludes that the efficient nutrient utilization and the lipid metabolic pathway occur at the optimum dietary lipid level of 8% in C. magur larvae.